Productivity potential of sesame in rabi-summer season under rice-fallow and turmeric-fallow: Productivity potential of sesame in rabi-summer season under rice-fallow and turmeric-fallow - G D SATISH KUMAR; A AZIZ QURESHI (Journal of Oilseeds Research, 2020)
The productivity potential of rabi-summer sesame was demonstrated in six districts of three states with adoption of improved technologies. The productivity increase with adoption of improved technologies under rice fallow situation was 22, 25 and 27% in Andhra Pradesh, Telangana and West Bengal respectively, whereas under turmeric fallow situation, the increase was 25% in West Bengal over farmer’s practice.